All-Cause Mortality up to and After Coronary Heart Disease and Stroke Events in European Middle-Aged Men. Issue 5 (May 2015) - Majed, Bilal; Montaye, Michèle; Wagner, Aline; Arveiler, Dominique; Ducimetiere, Pierre; Tafflet, Muriel; Ferrieres, Jean; Ruidavets, Jean-Bernard; Kee, Frank; Evans, Alun; Amouyel, Philippe; Prugger, Christof; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose— The aim was to investigate prospectively the all-cause mortality risk up to and after coronary heart disease (CHD) and stroke events in European middle-aged men. Methods— The study population comprised 10 424 men 50 to 59 years of age recruited between 1991 and 1994 in France (N=7855) and Northern Ireland (N=2747) within the Prospective Epidemiological Study of Myocardial Infarction. Incident CHD and stroke events and deaths from all causes were prospectively registered during the 10-year follow-up. In Cox's proportional hazards regression analysis, CHD and stroke events during follow-up were used as time-dependent covariates. Results— A total of 769 CHD and 132 stroke events were adjudicated, and 569 deaths up to and 66 after CHD or stroke occurred during follow-up. After adjustment for study country and cardiovascular risk factors, the hazard ratios of all-cause mortality were 1.58 (95% confidence interval 1.18–2.12) after CHD and 3.13 (95% confidence interval 1.98–4.92) after stroke. Conclusions— These findings support continuous efforts to promote both primary and secondary prevention of cardiovascular disease.